(untitled) (Research, Society and Development, 2021)
Botulinum toxin is attained through an anaerobic bacteria known as Clostridium botulinum and can be used for several purposes, from aesthetic purposes to the treatment of various diseases, such as in the rehabilitation of patients with facial paralysis. The aim of the present work is to show the importance and the effects of the application of botulinum toxin in patients with facial paralysis, as well as to analyze the indications and clinical applicability of the product. Researches were carried out from databases such as Google Scholar, Lilacs, Scielo, preferably between the period of 2000 and 2020, by searching for the following keywords: “Facial Paralysis”, “Botulinum toxin”, “Facial symmetry”, in which articles were selected with complete texts, written in Portuguese and in English. The use of botulinum toxin in the rehabilitation of patients with facial paralysis is raising more and more, and studies on the product are growing in order to achieve a single use protocol, even though it’s still noticeable the lackness of these studies. The rehabilitation of patients with facial paralysis who use botulinum toxin is effective and safe, and it can be na option to improve facial asymmetry.